The Impact of Multiple Intelligences Approach through Quantum Teaching Model toward The Scientific Attitude and Science Learning Outcomes in The Fourth Grade Students - Ratnasari, Ika Tiara; Wardani, Sri; Nuswowati, Murbangun (Journal of Primary Education, 2018)
The background of this research is less optimal learning of science grade IV of elementary school in Tugu subdistrict semester I of academic year 2017/2018. Students have not shown a good scientific attitude so that science learning achievement is not optimal yet. The classical passing grade of science is still less than 85%. For the same case, other researchers have applied a quantum teaching model with multiple intelligences to improve learning outcomes. The aim of this research is to know the impact of multiple intelligences approach through quantum teaching model to scientific attitude and science learning outcomes in the  fourth grade student on plant part structure material. This research was conducted at the SDN Tugurejo 01 and the SDN Tugurejo 03 Semarang academic year 2016/2017. This research method is true experimental design with pretest-posttest control group design model. The sampling technique chosen is probability sampling with simple random sampling model. The result on scientific attitude of experimental class is 78,4% belongs to a good category while the passing grade of science learning is 87,9% with average score 81. Result on scientific attitude of control class 70,97% belongs to medium category while passing grade of science learning 81.3% with an average of 76. The conclusion of this study is learning by multiple intelligences approach through quantum teaching model more effective to improve scientific attitudes and science learning outcomes than learning by quantum teaching model.